2021
DOI: 10.5267/j.jpm.2020.9.002
|View full text |Cite
|
Sign up to set email alerts
|

Competitive advantage to enhance internationalization and marketing performance woodcraft industry: A perspective of resource-based view theory

Abstract: The increasingly tight competition has caused problems for small and medium enterprises (SMEs) in increasing their marketing performance. During the last few years, the marketing performance of SMEs operating in the Project woodcraft industry sector in the Badung Bali has moved downwards. The goal of this research is to develop knowledge in the fields of Strategic Management, specifically regarding product innovation to achieve a competitive advantage in an attempt to improve internationalization and marketing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 1 publication
1
25
1
1
Order By: Relevance
“…The resource-based theory demands organizations effectively use their resources and skills to enhance productivity [4]. As a result, many organizations have shifted their paradigm from physical labor to "knowledge capital" such as knowledge workers, automation, and artificial intelligence, while many jobs that are formally done by humans are now being performed by machines [5].…”
Section: Introductionmentioning
confidence: 99%
“…The resource-based theory demands organizations effectively use their resources and skills to enhance productivity [4]. As a result, many organizations have shifted their paradigm from physical labor to "knowledge capital" such as knowledge workers, automation, and artificial intelligence, while many jobs that are formally done by humans are now being performed by machines [5].…”
Section: Introductionmentioning
confidence: 99%
“…That is, the intertwined individuals' actions with firm outcomes ought to be supported by a relevant theory (Coviello et al, 2017). In this regard, Resource-Based View (RBV) provides a theoretical framework to explore comprehend how international SMEs leverage their managerial resources and capabilities to attain and sustain competitive advantage (Lukovszki et al, 2020;Sukaatmadja et al, 2020). In particular, RBV proposes that managers' dynamic capabilities contribute to the identification, creation, and integration of crucial resources for SMEs' survival and growth (Hernández-Linares et al, 2018;Wu, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Budur and Poturak (2021) concluded that customer service performance has a significant positive influence on customers' loyalty and satisfaction that ultimately generate prominent marketing performance. Sukaatmadja, Yasa, Rahyuda, Setini, and Dharmanegara (2021) have investigated the role of competitive advantages to increase marketing performance and internationalization of the woodcraft industry, they determined that competitive advantages of customer service performance have significant positive effects on the marketing performance of the woodcraft industry. Moreover, research conducted on marketing performance focusing bread and cake industry determined that customer service performance play a crucial role in the marketing performance.…”
Section: Discussionmentioning
confidence: 99%